Effect of oxidation of catalytically active silicon-based electrodes on water decomposition - Primachenko, V.E.; Serba, O.A.; Chernobai, V.A.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
In this work, we continue to study the revealed phenomenon of current creation in the electrochemical system with distilled water during its decomposition without any applied external voltage. Investigated are catalytically active (to decompose water) electrodes based on silicon with modified surface (due to lapping, texturing, doping with palladium, creation of silicides) before and after thermooxidizing for 1 hour in dry oxygen at 850 ºC. Also performed are investigations of time dependences for the current between silicon electrodes and counter-electrodes made of Al, Pt, Yb when using the circuit with the external voltage V₀ = ± 9.7 V. Analyzed are the results obtained and prospects for a further study.